On weakly irreducible nonnegative tensors and interval hull of some classes of tensors. Issue 4 (2nd April 2016) - Rajesh Kannan, M.; Shaked-Monderer, Naomi; Berman, Abraham
Abstract : In this article, we prove the strict monotonicity of the spectral radius of weakly irreducible nonnegative tensors. As an application, we give a necessary and sufficient condition for an interval hull of tensors to be contained in the set of all strong -tensors. We also establish some properties of -tensors. Finally, we consider some problems related to interval hull of positive (semi)definite tensors and -tensors.